(untitled) (Journal of Hama University, 2026)
The current research aimed to identify the most significant difficulties in implementing the Montessori curriculum in public kindergartens from the perspective of teachers in Hama city. The research was conducted on a sample of (57) public kindergarten teachers in Hama city. Differences in their responses were identified based on the variable of educational level and the training courses the teacher underwent. For this purpose, a questionnaire consisting of (24) items was administered in four axes regarding the most significant difficulties in implementing the Montessori curriculum in public kindergartens from the teachers’ perspectives: (difficulties related to the environment and equipment in the kindergarten - difficulties related to the curriculum - difficulties related to the teacher - difficulties related to the child). The results showed a descending order of difficulties from the perspective of the research sample, with difficulties related to the child coming in first place, and difficulties related to the curriculum coming in last place. Furthermore, there were no statistically significant differences based on the variable of educational level, nor were there any statistically significant differences based on the variable of training courses. In light of the findings, the study presented several proposals, including the need to focus on the Montessori method and adopt it as a teaching method, given the importance of the method in the educational process. It also recommended providing Montessori materials to public kindergartens, and conducting free training courses for teachers on how to implement the Montessori method